(untitled) (Iraqi Journal of Medical Sciences, 2020)
Background:One of the commonest genetic subtypes of acute lymphoblastic leukemia (ALL) is t (12;21) (ETV6/RUNX1) being associated with favorable prognosis and distinctive clinical and pathological features. There are few studies about this abnormality in Iraq. Objective:To detect the expression ETV6/RUNX1 fusion gene in B-ALL pediatric patients by using FISH technique. Methods:This cross-sectional study was conducted from April 2018 to September 2018. Forty-eight newly diagnosed children with B-ALL were enrolled in this study. Fresh peripheral heparinized blood sample (3 ml) were taken from the patient at admission before chemotherapy, and ETV6-RUNX1 probe was applied and reading done by florescent microscope. Results:The mean age of study group was (4.01±0.19) years, their median age was 4.1 years, ranging between (2-7.2) years at diagnosis, ETV6/RUNX1 chimeric transcript product was found in 19 of 48 (39.6%) pediatric B- ALL patients. Conclusion:The frequency of investigated translocation [t(12;21)/ETV6/RUNX1 in a sample of Iraqi pediatric B-ALL patients, was among the higher reported frequencies worldwide, and that ETV6/RUNX1 fusion gene is independent prognostic factor not related to other hematological and clinical parameters. Keywords:ETV6/RUNX1 fusion gene, pediatric ALL, FISH Citation:Mahdi YM, Hameed BM, Mahmood FM, Qassim KW, Al-Mamoori HS. Detection of ETV6/RUNX1 fusion gene using FISH technique detection in pediatric all patients. Iraqi JMS. 2019; 17(3&4): 201-206. doi: 10.22578/IJMS.17.3&4.6